2015
DOI: 10.14260/jemds/2015/3
|View full text |Cite
|
Sign up to set email alerts
|

Local and Locoregional Flaps in Head and Neck Defects

Abstract: BACKGROUND: Local and locoregional flaps are very useful in reconstruction of head and neck defects. Each case should be judged on its merits and selection of flap (local or locoregional) should be done by considering various factors. AIM: To study the etiological factors, type, distribution, management of head and neck defects (post traumatic, post malignancy & congenital) by using local and locoregional flaps and the overall cosmetic effect and function of both donor as well as recipient sites. MATERIAL AND … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(9 citation statements)
references
References 15 publications
2
7
0
Order By: Relevance
“…However, in the present study none of forehead flap was found to reach beyond the midface. Nasolabial flap was reported by Multani et al, [3] as an ideal source for nasal reconstruction and the flap can reconstruct outer or inner lining of nasal defects in consistence with the current study. As regards to the safety to harvest island submental flap, during excision of the submandibular gland it must be performed with attention to the submental vessels on the superior glandular surface otherwise the pedicle could be injured [1].…”
Section: Technical Considerationssupporting
confidence: 76%
See 4 more Smart Citations
“…However, in the present study none of forehead flap was found to reach beyond the midface. Nasolabial flap was reported by Multani et al, [3] as an ideal source for nasal reconstruction and the flap can reconstruct outer or inner lining of nasal defects in consistence with the current study. As regards to the safety to harvest island submental flap, during excision of the submandibular gland it must be performed with attention to the submental vessels on the superior glandular surface otherwise the pedicle could be injured [1].…”
Section: Technical Considerationssupporting
confidence: 76%
“…Multani et al, reported in their review that nasolabial flaps in nasal reconstruction were the ideal source regarding color, nature and texture match. Furthermore, donor site morbidity is minimal owing to placing its scar along the nasolabial fold [3]. In the present study, also, we reported maximal color, nature and texture match with nasolabial flap in nasal reconstruction when achievable.…”
Section: Aesthetic Considerationssupporting
confidence: 72%
See 3 more Smart Citations